Adverse Selection and Convertible Bonds - Chakraborty, A.; Yilmaz, B. (Review of Economic Studies, 2011)
Informational asymmetries between a firm and investors may lead to adverse selection in capital markets. This paper demonstrates that when the market obtains noisy information about a firm over time, this adverse selection problem can be costlessly solved by issuing callable convertible bonds with restrictive call provisions. Such securities can be designed to make the payoff to new claimholders independent of the private information of the manager. This eliminates the possibility of any dilution of equity or underinvestment and implements the symmetric information outcome in either a pooling or a separating equilibrium. The same first-best efficient outcome can also be implemented by issuing floating-price and mandatory convertibles.